Best Damn Firewall Book Period - Carasik-Henmi, Anne (Syngress Publishing, 2011)
This book is essential reading for anyone wanting to protect Internet-connected computers from unauthorized access. Coverage includes TCP/IP, setting up firewalls, testing and maintaining firewalls, and much more. All of the major important firewall products are covered including Microsoft Internet Security and Acceleration Server (ISA), ISS BlackICE, Symantec Firewall, Check Point NG, and PIX Firewall. Firewall configuration strategies and techniques are covered in depth.